Besifovir therapy improves hepatic histology and reduces covalently closed circular DNA in chronic hepatitis B patients. Issue 2 (2nd November 2021) - Yim, Hyung Joon; Kim, Won; Ahn, Sang Hoon; Jung, Young Kul; Um, Soon Ho; Sohn, Joo Hyun; Jang, Jae Young; Kim, Dong Joon; Park, Eun‐Sook; Jin, So‐Young; Kim, Kyun‐Hwan
Abstract: Background and Aim: Besifovir dipivoxil maleate (BSV) was reported to have comparable antiviral efficacy and superior renal and bone safety to tenofovir disoproxil fumarate (TDF) in chronic hepatitis B (CHB) patients. The present study aims to evaluate changes of liver histology and intrahepatic covalently closed circular DNA (cccDNA) levels by BSV treatment in comparison with TDF therapy. Methods: This is a subset study of the phase 3 trial comparing BSV with TDF. Among them, only CHB patients willing to participate in a histologic evaluation study were enrolled. Liver histologic examination and intrahepatic cccDNA quantification were performed. Results: A total of 46 CHB patients received liver biopsies (BSV, n = 29; TDF, n = 17). After 48 weeks of treatment, virological response rate was comparable between the groups ( P = 0.707). Follow‐up liver biopsies showed that necroinflammation was significantly improved in the both groups. However, the histological response rate defined as the proportion of subjects whose modified histologic activity index score decreased by ≥ 2 without deterioration in fibrosis was higher in the BSV group than in the TDF group (77.8% vs 36.4%, P = 0.048). The proportion of subjects with Ishak fibrosis score 3 or more decreased from 77.7% to 55.5% in the BSV and that decreased from 72.7% to 45.4% in the TDF group. The intrahepatic cccDNA significantly decreased from baseline after 48 weeks of BSV or TDF treatment ( P < 0.001) without intergroup differences ( P = 0.349). Conclusions: The BSV therapy improves hepatic histology and decreases intrahepatic cccDNA in CHB patients.